Knowledge About Congenital Infections (Torch) Among Women in Sanaa Hospitals, Yemen, 2025 - Ali, Amat-Alsalam Bassam; Al-Qudaimi, Safwa Sami Hizam; Alhadha, Shaima Aiman; Alaqel, Alia Ali Yahia Hussein (My University, 2025)
Background: Congenital TORCH infections (Toxoplasmosis, Other infections, Rubella, Cytomegalovirus, and Herpes simplex virus) remain significant causes of perinatal morbidity and mortality worldwide. Inadequate knowledge among women of reproductive age increases the risk of preventable maternal and neonatal complications. Objective: To assess the level of knowledge regarding TORCH infections among women attending selected hospitals in Sana'a, Yemen, in 2025.